Model Gaya Hidup Konsumen Dalam Memilih Produk Makanan Dalam Negeri - Reny Andriyanty; Haswan Yunaz (JURNAL ILMIAH MANAJEMEN & BISNIS, 2020)
The research objection are to obtain information about the relationship between the young generation lifestyle that related to the domestic food and beverage products consumption  (case of warteg).  The research methods was  descriptive method with 100 samples. The data analyzed by mutlivariance analysis with structural equation modeling.  The developed research model 70.7 percent is represented by exogenous variables.  Consumption motives in the form of economic and social motives that developed in the young generation, the pleasant experiences of domestic food products consumption, the consumers' perceptions about ethnocentrism and consumer attitudes that appreciate the domestic product are influencing factors for “love domestic product “ lifestyle among the young generation.